1993
DOI: 10.1139/v93-156
|View full text |Cite
|
Sign up to set email alerts
|

Laser flash photolysis study of the photochemistry of ortho-benzoylbenzaldehyde

Abstract: . Ketene-enols 4 and 5 have been generated by laser flash photolysis of or-tho-benzoylbenzaldehytle (3) and kinetically and spectroscopically characterized. In benzene or acetonitrile, the E ketene-enol, 4, shows absorption at 340 and 400 nm and a lifetime in excess of 1 ms, whereas the Z ketene-enol, 5 , shows maxima at 360 and 430 nrn and a lifeti~iie of only 1.5 ks. At shorter time scales we observed a weak absorption (A,,,;,, = 580 nm) tentatively assigned to biradical 6 with a lifetime of 140 ns. The E ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…The rate constant for quenching of the E-ketene-enol (from 2-benzoylbenzaldehyde) by water has been found by Netto-Ferreira and Scaiano to be 1.1 × 10 3 M -1 s -1 in acetonitrile. 50 In conclusion, Scheme 6 shows a complete mechanistic proposal of the photochemical transformation of 1a into the major products 3a and 2. It includes short-lived transients detected by LFP, productive or nonproductive isolated as well as hypothetical intermediates, and byproducts, such as methanol, methyl chloride, or the acetophenone derivative 5a that is produced in traces, apparently by homolytic C-Cl bond cleavage.…”
Section: -Alkoxymethyl-5-methylphenacyl Chloride and Benzoatementioning
confidence: 88%
See 1 more Smart Citation
“…The rate constant for quenching of the E-ketene-enol (from 2-benzoylbenzaldehyde) by water has been found by Netto-Ferreira and Scaiano to be 1.1 × 10 3 M -1 s -1 in acetonitrile. 50 In conclusion, Scheme 6 shows a complete mechanistic proposal of the photochemical transformation of 1a into the major products 3a and 2. It includes short-lived transients detected by LFP, productive or nonproductive isolated as well as hypothetical intermediates, and byproducts, such as methanol, methyl chloride, or the acetophenone derivative 5a that is produced in traces, apparently by homolytic C-Cl bond cleavage.…”
Section: -Alkoxymethyl-5-methylphenacyl Chloride and Benzoatementioning
confidence: 88%
“…52,53 For 2-benzoylbenzaldehyde in benzene or acetonitrile intramolecular hydrogen transfer leads to the formation of two ketene-enols: E (τ ) 1 ms), showing absorption at 340 and 400 nm, and Z (τ ) 1.5 µs) with λ max ∼ 360 and 430 nm. 50 By analogy, we assign the transient with λ max ) 400 nm to Z-9 and that with λ max ) 370 nm to E-9 (Table 4; Scheme 6). The lifetime of E-9 is reduced in aerated solutions, which may indicate oxidation by O 2 , as observed in the study on 2-phthalaldehyde.…”
Section: -Alkoxymethyl-5-methylphenacyl Chloride and Benzoatementioning
confidence: 99%
“…17 It was observed that addition of water shortens the lifetime of the longlived transient without leading to additional photoproducts. Water molecules may for example act as catalysts for certain reaction steps.…”
Section: Discussionmentioning
confidence: 99%
“…6 A ketene intermediate was indeed observed via IR spectroscopy in a matrix isolation experiment. Time resolved spectroscopy on oPA and related compounds 15,17,18 lacked the temporal resolution to trace the ketene formation. Time resolved spectroscopy on oPA and related compounds 15,17,18 lacked the temporal resolution to trace the ketene formation.…”
Section: Introductionmentioning
confidence: 99%
“…Suitably substituted aromatic ketones can form the corresponding benzocyclobutenols in fairly high quantum yields, suggesting that intramolecular [2+2] cycloaddition may be a more common process in photoen01 chemistry than had been previously assumed (6)(7)(8)(9). Other examples include chloride elimination from a-chloro acetophenones with the concomitant formation of 1-indanones (10)(11)(12), the formation of 3-phenylphthalide from the photolysis of ortho-benzoylbenzaldehyde (13), and, finally, the synthesis of 2-hydroxy-2-alkyl(or ary1)-1-indanones from ortho-alkyl substituted aromatic a-diketones (14)(15)(16)(17)(18) ysis and product studies on the photoenols in different solvents, generated by irradiation of ortho-benzylbenzophenone (1).…”
Section: Introductionmentioning
confidence: 99%